2019
DOI: 10.24874/ijqr13.02-14
|View full text |Cite
|
Sign up to set email alerts
|

Leadership Agility, the Influence on the Organizational Learning and Organizational Innovation and How to Reduce Imitation Orientation

Abstract: This research aims to test and analyze the significant positive effect of leadership agility toward organizational learning and organizational innovation; and organizational learning toward organizational innovation. It also test and analyze the significant negative effect of organizational innovation toward imitation orientation.The analysis is focused on 170 owner and manager of Batik MSMEs (micro small medium enterprises) in Pekalongan that known as Batik City worldwide. The statistic technique that is used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…This is important since some research findings reveal that leadership can moderate the influence of contingency variables with organizational performance (Yeh et al, 2016;Ximenes et al, 2019;Sari, 2013;Hutagalung, 2016). Muafi and Uyun (2018) found that leadership agility can be used to increase organizational innovation and reduce imitation behavior. Leaders must be able to seize opportunities amid increasing uncertainty and complexity, and they must have priorities for success (Muafi & Uyun, 2018;Joiner, Josephs, 2007;Joiner, 2009a;2009b;Lediju, 2016;Rizan et al, 2020).…”
Section: The Moderation Role Of Leadership Agilitymentioning
confidence: 99%
See 2 more Smart Citations
“…This is important since some research findings reveal that leadership can moderate the influence of contingency variables with organizational performance (Yeh et al, 2016;Ximenes et al, 2019;Sari, 2013;Hutagalung, 2016). Muafi and Uyun (2018) found that leadership agility can be used to increase organizational innovation and reduce imitation behavior. Leaders must be able to seize opportunities amid increasing uncertainty and complexity, and they must have priorities for success (Muafi & Uyun, 2018;Joiner, Josephs, 2007;Joiner, 2009a;2009b;Lediju, 2016;Rizan et al, 2020).…”
Section: The Moderation Role Of Leadership Agilitymentioning
confidence: 99%
“…Muafi and Uyun (2018) found that leadership agility can be used to increase organizational innovation and reduce imitation behavior. Leaders must be able to seize opportunities amid increasing uncertainty and complexity, and they must have priorities for success (Muafi & Uyun, 2018;Joiner, Josephs, 2007;Joiner, 2009a;2009b;Lediju, 2016;Rizan et al, 2020).…”
Section: The Moderation Role Of Leadership Agilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Pekalongan has been known to have a very large number of creative MSME which are spread evenly in almost every region. Besides that, Pekalongan is known as a city that has majority Muslim community which live side by side with non-Muslim communities and live in harmony with Arabs, Chinese and Indians ethnic (Muafi & Uyun, 2019). They have a talent as a designer or batik craftmen who is very well known and passed down from one generation to the next.…”
Section: Introductionmentioning
confidence: 99%
“…Not to mention they also have technological savvy, which is the ability of to use a device or technology properly and correctly to finally provide positive impacts on the environment and society. Nevertheless, a leader is not only seen from the level or only in high organizational positions (Uyun, 2018). There are two objects in the research.…”
Section: Introductionmentioning
confidence: 99%